2019
DOI: 10.37237/relay/020128
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Basic Psychological Needs in a Language Learning Center. Part 2: The Autonomy-Supportive Nature and Limitations of a SALC

Abstract: Basic Psychological Needs Theory (BPNT) is one of several mini theories within Self-Determination Theory, a framework developed by Deci and Ryan’s (1985) to study human motivation. As part of a larger, on-going project, the three main components of BPNT, autonomy, relatedness and competence, are used as points of evaluation to determine the autonomy-supportiveness of a Japanese self-access learning center (SALC). Based on the analysis of 107 interviews, we will highlight how the SALC is structured to be an aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Although using an English lounge has such benefits, some studies have observed that those who utilize such facilities frequently are the intermediate to highintermediate learners (e.g. Kawamura, 2009), more confident students with strong ideal L2 selves (Gillies, 2010), or highly autonomous, self-directed learners (Murray, 2017;Yarwood, Lorentzen, et al, 2019). While at the same time, a large number of studies in second language acquisition (SLA) have highlighted that foreign language anxiety can hinder L2 use (Horwitz, 2001;Horwitz et al, 1986).…”
Section: Sachi's Reflective Journal On Her First Visitmentioning
confidence: 99%
“…Although using an English lounge has such benefits, some studies have observed that those who utilize such facilities frequently are the intermediate to highintermediate learners (e.g. Kawamura, 2009), more confident students with strong ideal L2 selves (Gillies, 2010), or highly autonomous, self-directed learners (Murray, 2017;Yarwood, Lorentzen, et al, 2019). While at the same time, a large number of studies in second language acquisition (SLA) have highlighted that foreign language anxiety can hinder L2 use (Horwitz, 2001;Horwitz et al, 1986).…”
Section: Sachi's Reflective Journal On Her First Visitmentioning
confidence: 99%
“…Several mini-theories within SDT have received substantial attention in the research literature, demonstrating how humans can thrive when optimal conditions are present (Reeve, 2016;Ryan & Deci, 2017). One of the mini theories that has frequently been applied in education-and recently to both advising (Shelton-Strong, 2022a, 2022bShelton-Strong & Tassinari, 2022) and self-access (Mynard, 2022;Mynard & Shelton-Strong, 2020, 2022Yarwood et al, 2019)-is basic psychological needs theory. In this theory, the three basic psychological needs of autonomy, competence and relatedness must be satisfied to create optimal conditions for wellness and effective functioning.…”
Section: Theoretical Framework: Self-determination Theory (Sdt)mentioning
confidence: 99%
“…Phillip A. Bennett and Amelia Yarwood I n the final presentation, Phillip A. Bennett and Amelia Yarwood introduced findings from an action research project (Yarwood et al, 2019;Bennett & Yarwood, 2021) that used targeted discussion prompts used twice-weekly in a single, synchronous online classroom to inspire a more self-aware, positive social climate. It was anticipated that if learners could share their experiences, worries, and ideas about common language learning issues (e.g., the fear of making mistakes, difficulties in focussing during online classes), they could build a supportive online classroom environment within which L2 willingness to communicate (L2 WTC) is facilitated.…”
Section: Fostering Relatedness Between Students In Online Classrooms ...mentioning
confidence: 99%